Vascular endothelial growth factor (VEGF) expression in induction phase chemotherapy of acute lymphoblastic leukemia - Dasril Daud; Merlyn Meta Astari; Nadirah Rasyid Ridha (Paediatrica Indonesiana, 2019)
Background Leukemia is a hematolymphoid malignancy originating from bone marrow. The progression of hematolymphoid malignancies depends on new formation of vasculature, called angiogenesis. Angiogenesis is regulated by vascular endothelial growth factor (VEGF), which is secreted by paracrine and autocrine signaling mechanisms. Objective To evaluate VEGF expression in induction phase chemotherapy of acute lymphoblastic leukemia (ALL) patients. Methods This prospective, cohort study was conducted in ALL patients admitted to Dr. Wahidin Sudirohusodo Hospital, Makassar, South Sulawesi, from October 2016 to October 2017. Subjects’ VEGF levels were measured at diagnosis and at the end of induction chemotherapy. Results VEGF levels were analyzed in 59 patients, 29 of whom were diagnosed with standard risk ALL and 30 patients with high risk ALL. VEGF levels were significantly decreased after induction phase chemotherapy in standard risk ALL and in high risk ALL subjects. There was no significant difference in VEGF levels before induction phase chemotherapy between the standard and high risk groups (P=0.405). There was also no significant difference in VEGF levels after induction phase chemotherapy between the two risk groups (P=0.094). Conclusion The VEGF level is significantly lower after ALL induction phase chemotherapy in both the standard risk and high risk ALL groups. However, there are no significant differences in VEGF levels between the standard and high risk groups before as well as after induction phase chemotherapy.